2006
DOI: 10.1007/s00223-006-0126-z
|View full text |Cite
|
Sign up to set email alerts
|

Calcification Inhibitors and Wnt Signaling Proteins Are Implicated in Bovine Artery Smooth Muscle Cell Calcification in the Presence of Phosphate and Vitamin D Sterols

Abstract: Administration of active vitamin D sterols to treat secondary hyperparathyroidism in patients with chronic kidney disease receiving dialysis has been associated with elevated serum calcium and phosphorus levels, which may lead to increased risk of vascular calcification. However, calcimimetics, by binding to the parathyroid gland calcium-sensing receptors, reduce serum parathyroid hormone, calcium, phosphorus, and the calcium-phosphorus product. Using cultured bovine aorta vascular smooth muscle cells (BASMCs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 51 publications
4
42
0
Order By: Relevance
“…Hyperphosphatemia is linked to cardiovascular risk as well as bone disease (19,20), and the hyperphosphatemic milieu may promote vascular calcification through cellular changes in vascular smooth muscle cells (21). Previous open-label studies by Takahashi et al (10) and Sampathkumar et al (22) demonstrated that niacinamide lowers serum phosphorus levels in maintenance hemodialysis patients when traditional binding agents are withheld.…”
Section: Discussionmentioning
confidence: 99%
“…Hyperphosphatemia is linked to cardiovascular risk as well as bone disease (19,20), and the hyperphosphatemic milieu may promote vascular calcification through cellular changes in vascular smooth muscle cells (21). Previous open-label studies by Takahashi et al (10) and Sampathkumar et al (22) demonstrated that niacinamide lowers serum phosphorus levels in maintenance hemodialysis patients when traditional binding agents are withheld.…”
Section: Discussionmentioning
confidence: 99%
“…42 In the VDR −/− and Low-Density Lipoprotein receptor −/− mouse model, a low vitamin D diet increased aortic calcification via a mechanism involving upregulation of osteoblast transcription factors. 44 These differences in the influence of 1,25(OH) 2 D or its analogs on both calcification and the gene expression of calcification factors may be pharmacological rather than physiological. Because vitamin D is activated to 1,25(OH) 2 D in the kidney, uremia changes homeostatic mechanisms, where vitamin D signaling plays a critical role, with vitamin D agonists offering therapeutic benefits.…”
Section: Vascular Calcificationmentioning
confidence: 99%
“…VSMCs express the vitamin D receptor and have functional 1-a hydroxylase and 25-hydroxylase enzyme systems so that all vitamin D metabolites can be utilized by them in an autocrine/paracrine fashion. 71 VDRAs promote calcification by upregulating Runx2, osterix, and osteocalcin 72,73 and also increasing calcium transport into the VSMCs. 74 However, other studies show that vitamin D has protective effects by increasing calcification inhibitory proteins such as MGP and osteopontin, 75 reducing proinflammatory cytokines, such as IL-6, IL-1b, and TGF-b.…”
Section: Fgf-23-klotho and Vascular Senescencementioning
confidence: 99%